Peningkatan Tahap Keselamatan di Tapak Bina dengan Pengaplikasian Teknologi Dron - Mohd Rizal, Muhammad Naqib Amsyar; Masrom, Md Asrul Nasid; Seow, Ta Wee; Kasim, Narimah; Omar, Roshartini (Research in Management of Technology and Business, 2024)
The construction industry is known for its complex and dangerous work environment, where safety risks abound and can lead to accidents, injuries, and even deaths. Ensuring safety on a construction site is of utmost importance to protect the well-being of workers and minimize project disruptions. One such technology that has gained significant attention is drone technology. Drone technology is an unmanned aerial vehicle (UAV) or also known as a flying robot. Real-time monitoring is another important aspect where drone technology can make a big impact in improving safety on construction sites. The purpose of this study is to examine the function of using drones on construction sites. The next idea is to identify the level of security in the construction site area with the application of drones. This study uses a qualitative approach. This study will use the interview method to obtain information. The respondents are made up of G7 contractors from. This study was conducted around the Klang Valley area because the development in that area is very rapid. The data analysis method used is the thematic method. The results of the study show that there is an increase in the level of safety at the construction site with the application of drones. The hope from this study is that the use of drone technology in the construction industry in Malaysia can be improved to ensure that the level of safety performance at construction sites improves. The use of this technology can facilitate a work matter where it can reduce time, manpower and risk employee.